Muon sites and muon states in model fluorides and magnets - Wilkinson, J (2022)
The F–μ–F state occurs when a spin polarised muon implanted in a fluoride crystal becomes entangled with its nearest neighbour fluorine nuclei, resulting in a beating pattern observed in the muon decay asymmetry. Ever since these states were discovered in the 1980s, they have never been fully understood, as fitting the data always required a phenomenological relaxation function to account for the observed decay of the oscillations.